Differential responses of soil bacteria, fungi, archaea and protists to plant species richness and plant functional group identity - Dassen, Sigrid; Cortois, Roeland; Martens, Henk; Hollander, Mattias; Kowalchuk, George A.; Putten, Wim H.; De Deyn, Gerlinde B. (Molecular ecology, 2017)
Plants are known to influence belowground microbial community structure along their roots, but the impacts of plant species richness and plant functional group (FG) identity on microbial communities in the bulk soil are still not well understood. Here, we used 454‐pyrosequencing to analyse the soil microbial community composition in a long‐term biodiversity experiment at Jena, Germany. We examined responses of bacteria, fungi, archaea, and protists to plant species richness (communities varying from 1 to 60 sown species) and plant FG identity (grasses, legumes, small herbs, tall herbs) in bulk soil. We hypothesized that plant species richness and FG identity would alter microbial community composition and have a positive impact on microbial species richness. Plant species richness had a marginal positive effect on the richness of fungi, but we observed no such effect on bacteria, archaea and protists. Plant species richness also did not have a large impact on microbial community composition. Rather, abiotic soil properties partially explained the community composition of bacteria, fungi, arbuscular mycorrhizal fungi (AMF), archaea and protists. Plant FG richness did not impact microbial community composition; however, plant FG identity was more effective. Bacterial richness was highest in legume plots and lowest in small herb plots, and AMF and archaeal community composition in legume plant communities was distinct from that in communities composed of other plant FGs. We conclude that soil microbial community composition in bulk soil is influenced more by changes in plant FG composition and abiotic soil properties, than by changes in plant species richness per se.